1990
DOI: 10.1111/j.1476-5381.1990.tb14676.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nootropic drug oxiracetam on field potentials of rat hippocampal slices

Abstract: 1 The effect of the nootropic drug oxiracetam on hippocampal neurotransmission was investigated in the CAI region of the rat hippocampal slice in vitro by use of extracellular recordings.2 Superfusion of oxiracetam (0.1-1001iM) produced a concentration-dependent, wash-resistant (>90 min), increase in initial slope and amplitude of the dendritic field excitatory postsynaptic potential (e.p.s.p.). This increase was maximal at a concentration of 1 YM (70%). 3 Input-output curves relating the initial slope to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Benzodiazepine inverse agonists also have been reported to enhance cognition (Venault et al, 1986;Lorez et al, 1988;Sarter et al, 1988a;Sarter & Stecker, 1989) and these compounds stimulate HACU after in vivo drug treatment (Miller & Chmielewski, 1990 reported for several potential nootropic agents (Shih & Pugsley, 1985;Spignoli et al, 1986;Nakahiro et al, 1988) suggesting that this may be a common mechanism for cognition enhancement among a diverse number of compounds. (Bowen et al, 1976;Arendt et al, 1983 Several studies have demonstrated that drugs with cognition enhancing potential can enhance LTP in the hippocampus (Olpe & Lynch, 1982;Ito et al, 1988;Tanaka et al, 1989;Pugliese et al, 1990). It has been suggested that inhibition of interneurones may underlie increased excitability in the hippocampus (Bilkey & Goddard, 1985 Moran et al (1992).…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepine inverse agonists also have been reported to enhance cognition (Venault et al, 1986;Lorez et al, 1988;Sarter et al, 1988a;Sarter & Stecker, 1989) and these compounds stimulate HACU after in vivo drug treatment (Miller & Chmielewski, 1990 reported for several potential nootropic agents (Shih & Pugsley, 1985;Spignoli et al, 1986;Nakahiro et al, 1988) suggesting that this may be a common mechanism for cognition enhancement among a diverse number of compounds. (Bowen et al, 1976;Arendt et al, 1983 Several studies have demonstrated that drugs with cognition enhancing potential can enhance LTP in the hippocampus (Olpe & Lynch, 1982;Ito et al, 1988;Tanaka et al, 1989;Pugliese et al, 1990). It has been suggested that inhibition of interneurones may underlie increased excitability in the hippocampus (Bilkey & Goddard, 1985 Moran et al (1992).…”
Section: Discussionmentioning
confidence: 99%
“…The U-shaped dose-action curve of piracetam found in the present study is common among nootropics. In the literature, a considerable number of studies mention the fact that piracetam in lower doses exerts a significant effect while in higher doses the effect may either dissipate until it completely disappears (Satoh et al, 1986;Marchi et al, 1990;Pugliese et al, 1990;Pizzi et al, 1993) or reverse direction (Raiteri et al, 1992;Spignoli et al, 1986), resulting in a reversed dose-response curve or a U-or bell-shaped curve respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is the main neurotransmitter of excitatory cell signal processes and its release after cell depolarization has been shown to be potentiated by nootropics (Marchi et al, 1990). Moreover, nootropics enhance neurotransmission of the different types of glutamate receptors (Pugliese et al, 1990;Tang et al, 1991;Copani et al, 1992;Tsuzuki et al, 1992). Since several recent studies suggest that the EAA system is also involved in opioid action, both after acute immobilization stress (Tocco et al, 1991) and in tolerance and withdrawal conditions (Akaoka & Aston-Jones, 1991;Aghajanian et al, 1994), and since NMDA-antagonists can attenuate morphine-induced tolerance (Marek et al, 1991;Trujillo & Akil, 1991;Tiseo & Inturrisi, 1993), it is possible that it is through this EAA system that piracetam exerts its effects on opioid stress and tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effects of pyrrolidone deriva tives may be related to the enhancement of brain cholinergic mechanisms. In addition, ox iracetam and other pyrrolidone derivatives have been shown to augment hippocampal long-term potentiation in rats (6) and guinea pigs (7,8). These investigations suggest that pyrrolidone derivatives enhance cerebral func tion in normal brain and protect it in impaired brain.…”
mentioning
confidence: 89%